Post-Traumatic Cities: The Sense of Inclusiveness and the Impact of Universal Design, Beirut from 1960 until 2024 - Maria A. El Helou (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The aim of this study is to treat a significant gap found in Beirut in 2024: enhancing its inhabitants’ sense of inclusiveness in its public spaces. One effective potential approach posited to achieve this aim is the implementation of Universal Design (UD). A questionnaire was distributed to 150 Biartis in order to understand what in their eyes are the changes in public spaces impacting the urban connectivity of Beirut and its inhabitants use of these spaces, from 1960 until 2024. The findings revealed that the prewar sense of inclusiveness in Beirut was higher and that major reasons for a lack of inclusiveness and urban connectivity include the lack of UD implementation tackling both the types of vulnerability and disability specific to the post-disaster Beirut and the evolution of the war-created urban fragmentation. The results contribute in defining the specific UD to implement to enhance the sense of inclusiveness in Beirut.